2014
DOI: 10.5032/jae.2014.04148
|View full text |Cite
|
Sign up to set email alerts
|

Learning Activities Utilized and Readiness for the Student Teaching Internship

Abstract: Agricultural education has traditionally provided rich learning experiences for secondary school students; however, less attention has been paid to the learning experiences preservice agricultural education teachers utilize and provide secondary school students during the student teaching internship. This study sought to describe the learning activities preservice teachers utilize during instruction and assess preservice teachers ' self-perception of preparedness in technical content knowledge and teaching m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In terms of teaching style, Stripling, Thoron, and Estepp (2014) noted student teachers often "used student-centered activities with the greatest frequency" (p. 158), thus indicating that student teaching offers the opportunity for student teachers "to follow through with their preferred method and extend student-centered lessons into the authentic experience -their student teaching internship" (p. 158). Interestingly, Stripling et al (2014) also found student teachers often do not feel prepared to teach science-oriented technical agriculture content such as food science, biotechnology, and veterinary science after completing their student teaching experience. Moreover, as detailed by Krysher, Robinson, Montgomery, and Edwards (2012), student teachers can recognize challenges and successes during the student teaching experience.…”
Section: Introduction and Conceptual Frameworkmentioning
confidence: 99%
“…In terms of teaching style, Stripling, Thoron, and Estepp (2014) noted student teachers often "used student-centered activities with the greatest frequency" (p. 158), thus indicating that student teaching offers the opportunity for student teachers "to follow through with their preferred method and extend student-centered lessons into the authentic experience -their student teaching internship" (p. 158). Interestingly, Stripling et al (2014) also found student teachers often do not feel prepared to teach science-oriented technical agriculture content such as food science, biotechnology, and veterinary science after completing their student teaching experience. Moreover, as detailed by Krysher, Robinson, Montgomery, and Edwards (2012), student teachers can recognize challenges and successes during the student teaching experience.…”
Section: Introduction and Conceptual Frameworkmentioning
confidence: 99%
“…Agricultural mechanics teachers must have knowledge dealing with a wide array of curriculum (Saucier, McKim, & Tummons, 2012); they must also account for discrepancies in learners' ability, prior knowledge, needs, and experiences (Rayfield, Croom, Stair, & Murray, 2011). Although laboratory management skills are essential knowledge for all school-based agricultural mechanics teachers (Saucier, Terry Jr., & Schumacher, 2009), many preservice teachers report inadequate content knowledge in Agricultural Mechanics subject areas (Stripling, Thoron, & Estepp, 2014).…”
mentioning
confidence: 99%
“…Agricultural mechanics knowledge issues are compounded by a lack of adequate training, professional development, and instructional materials in agricultural safety (Rudolphi & Retallick, 2015). Specifically, agricultural programs have reduced the amount of training received in courses specific to agricultural mechanics (Burris et al, 2005;Schumacher, Ess, Strickland, & King, 2002), and teachers across multiple geographic regions and teaching experience levels have reported a need for professional development related to agricultural mechanics (Blackburn, Robinson, & Field, 2015;Duncan, Ricketts, Peake, & Uesseler, 2006;Stripling et al, 2014). Among the many professional development needs of agricultural mechanics teachers, safety instruction and supervision is a top concern while in the agricultural mechanics laboratory (Gliem & Miller, 1993;Johnson & Schumacher, 1988;Langley & Kitchel, 2013;Swan, 1992).…”
mentioning
confidence: 99%
“…As a link in the model, Teacher Preparation and Certification is a critical component in ensuring students are prepared in agriculture technology (Rosencrans & Martin, 1997). Agricultural education teachers perceived preservice instruction in agricultural mechanics to be important, but the preparation they received at the postsecondary level was not adequate for the duties a SBAE position requires (Burris et al, 2005;Stripling et al, 2014). Much of the learning that takes place in an agricultural mechanics course occurs in a laboratory, requiring educators to be proficient in agricultural mechanics skills (Saucier et al, 2012).…”
Section: Conclusion Recommendations and Implicationsmentioning
confidence: 99%